Ultrafast deep-ultraviolet spectroscopy of ionised liquid water - Ng, Zi Xuan (2020)
The ionisation of liquid water is a phenomenon that accompanies high-energy radiation with biological systems and aqueous solutions. The study of this process is of fundamental importance to radiation biology and radiation chemistry.[1-3] Upon photoionisation, a water radical cation, H2O●+, is produced upon an ejection of an electron which subsequently relaxes into the localized hydrated electron, ehyd-. The H2O●+ radical cation undergoes a proton transfer reaction to yield a hydroxyl radical, ●OH and a hydronium ion, H3O+. Previous studies have measured the timescale of decay of the H2O●+ radical cation to be 46 fs.[4] To build on that discovery, this study focuses on detecting the formation time of the proton transfer product, the ●OH radical, by monitoring its deep-ultraviolet (DUV) absorption. Herein, this study presents the successful generation of ultrashort DUV pulses, and the ultrafast pump-probe spectroscopic measurements of the absorption of the ●OH radical.